Genetic data and underlying taxa and GenBank sources of diatoms used in phylogenetic analysis of Aneumastus mongolotusculus sp. nov. - Yevhen Maltsev; Svetlana Andreeva; Julia Podunay; Maxim Kulikovskiy (PANGAEA, 2019)
For the first time, the phylogenetic position of the genus Aneumastus D.G. Mann & Stickle is studied using molecular methods. In this manuscript we describe a new species, Aneumastus mongolotusculus Maltsev, Andreeva & Kulikovskiy sp. nov. from Lake Hovsgol in Mongolia, based on molecular and morphological investigations. The phylogenetic analysis (region V4 18S rDNA and partial rbcL gene) of the genus Aneumastus shows that the new taxon is closely related to the genus Mastogloia Thwaites and that Aneumastus should be included in the order Mastogloiales erected by Round et al. (1990).
Supplement to: Maltsev, Y et al. (2019): Description of Aneumastus mongolotusculus sp. nov. (Bacillariophyceae, Mastogloiales) from Lake Hovsgol (Mongolia) on the basis of molecular and morphological investigations. Nova Hedwigia, 148, 21-33, https://doi.org/10.1127/nova-suppl/2019/035